Sports talent identification based on motor tests and genetic analysis - Šimonek, J.; Židek, R. (Trends in Sport Sciences, 2018)
Physical tests have long been used for determining a child`s athletic abilities before age 9. At that age children are not yet physically mature and their motor skills are being developed. That is why the genetic test can come in [handy] for looking for early indicators of talent in performance areas. Aim of Study. The study aims at explaining the role of physical fitness testing and genetic analysis upon identifying sport talents. We hypothesized that using physical fitness tests will not bring the results which would match up with the ones of genetic analysis. This presumption was verified using motor tests battery and gene analysis in 7 year old population. Material and Methods. The research sample included 169 pupils (97 male; mean age = 7.438 y. and 72 female; mean age = 7.227 y.) attending 3 elementary schools in the region of Nitra, Slovakia. All pupils underwent 9 physical tests to determine their general physical abilities. Each performance of pupils in tests was allotted points. Subsequently, 30 best ranked pupils were selected to undergo 2 ml saliva sampling for genetic analysis. The values of individual genetic score are compared with histogram of genetic score distribution in European population. Results and Conclusions. The study showed that the results of genetic analysis did not match the ones of the fitness tests. Based on the analysis we offered parents and coaches valid information about their children`s prerequisites for certain group of sports, type of muscle fiber, oxidative capacity, nutrition type, regeneration, injury prevention, injury susceptibility, etc